Effect of Lecanicillium lecanii on date palm scale, Parlatoria blanchardi in date groves of Kachchh, Gujarat, India - Muralidharan, C.M.; Baidiyavadra, D.A.; Sharma, Kapil Mohan (Journal of Plantation Crops, 2020)
-